Darkened Leaves Use Different Metabolic Strategies for Senescence and Survival. Issue 1 (9th March 2018) - Law, Simon R.; Chrobok, Daria; Juvany, Marta; Delhomme, Nicolas; Lindén, Pernilla; Brouwer, Bastiaan; Ahad, Abdul; Moritz, Thomas; Jansson, Stefan; Gardeström, Per; Keech, Olivier
Abstract : A robust working model delineates the main axes of the divergent metabolic strategies used by Arabidopsis thaliana in response to partial or total darkening treatments. Abstract: In plants, an individually darkened leaf initiates senescence much more rapidly than a leaf from a whole darkened plant. Combining transcriptomic and metabolomic approaches in Arabidopsis ( Arabidopsis thaliana ), we present an overview of the metabolic strategies that are employed in response to different darkening treatments. Under darkened plant conditions, the perception of carbon starvation drove a profound metabolic readjustment in which branched-chain amino acids and potentially monosaccharides released from cell wall loosening became important substrates for maintaining minimal ATP production. Concomitantly, the increased accumulation of amino acids with a high nitrogen-carbon ratio may provide a safety mechanism for the storage of metabolically derived cytotoxic ammonium and a pool of nitrogen for use upon returning to typical growth conditions. Conversely, in individually darkened leaf, the metabolic profiling that followed our 13 C-enrichment assays revealed a temporal and differential exchange of metabolites, including sugars and amino acids, between the darkened leaf and the rest of the plant. This active transport could be the basis for a progressive metabolic shift in the substrates fueling mitochondrial activities, which are central to the catabolic reactions facilitating the retrieval of nutrients from the senescing leaf. We propose a model illustrating the specific metabolic strategies employed by leaves in response to these two darkening treatments, which support either rapid senescence or a strong capacity for survival.